Rdzogs pa chen po sku gsum rań śar gyi khrid gdams skor; texts outlining the initial practices for the followers of the precepts of the Bon-po Rdzogs-chen A-khrid - Bkra-śis-rgyal-mtshan, Śar-rdza, 1859-1933 (distributor: Tibetan Bonpo Monastic Centre, Dolanji, H.P., 1974)
Esoteric texts of the Bonpo Dzogchen tradition of Tibetan Lamaism.